A multiplicity result for critical elliptic problems involving differences of local and nonlocal operators - Perera, Kanishka; Sportelli, Caterina (Topological Methods in Nonlinear Analysis, 2024)
We study some critical elliptic problems involving the difference of two nonlocal operators, or the difference of a local operator and a nonlocal operator. The main result is the existence of two nontrivial weak solutions, one with negative energy and the other with positive energy, for all sufficiently small values of a parameter. The proof is based on an abstract result recently obtained in MR4293883.